The continuance of external review information system adoption in Malaysia / Mohd Norafizal Abd Aziz ... [et al.] - Abd Aziz, Mohd Norafizal; Razali, Razulaimi; Abdullah, Nik Rosli; Abdullah, Shahrul Azam (2021)
Industrial relation 4.0 has penetrated digitalisation and seamless technology into the current organisational practices in higher learning institutions in Malaysia. Therefore, the quality initiative has to adhere to the importance of the seamless technology adopted and practices. External review initiates the internal quality evaluation in UiTM conducted by the InQKA, SKKO department. The external audit has to be conducted annually for the selected faculty and branch campuses. The external review report is mandatory for the SKKO and University to record continual improvements in the quality activities. However, due to the increase in the number of faculty and branch campuses to be evaluated every year and due to the pandemic restrictions, issues raised regarding the late preparation and cost have penetrated the unsystematic external review final reporting process. Therefore, due to the advantage of seamless technology opportunities, the External Review Information System (ERIS) has taken place. ERIS has been developed using a cloud-based development and has been implemented in the current external review process in UiTM. Currently, ERIS is used to cater reporting on the external review of 18 faculties and branch campuses in UiTM as data recorded in 2020. The overall preparation of the external review report was recorded in less than 20 days compared to the previous approach. Hence, ERIS has contributed to solving the main issues and becoming a system used in the external review process. This paper will discuss the development and the implementation of ERIS and the contribution of this cloud-based system that may benefit the external review implementation. These findings will benefit the external review practices in Malaysia, mostly in the higher learning, which is merely important during the worldwide COVID-19 pandemic.